Use of Cedrela odorata gum exudate in the preparation of meat products - Ferrer de Chacín, Diana; Márquez Salas, Enrique; León de Pinto, Gladys (Rev. Téc. Fac. Ing. Univ. Zulia, 1970)
The use of Cedrela odorata gum exudate in the preparation of low fat meat products to improve their yield and stability was evaluated. Gum solubility in water and saline solution were determined at variable concentrations (0.5% ”“ 4.0%) and temperatures (5, 25 and 75°C). The yields of cooked ham and bologna, and the stability of the last product were measured in the presence of gum (0%, 0.5%, 1.0% and 2.0%). The yield of cooked ham, in seven treatments, with solid and dissolved gum (0%, 0.25%, 0.5% and 1.0%) was measured. Comparison of the yield of ham, using gum, starch and wheat flour was made. The results indicated that gum has good solubility in water and is partially soluble in saline solution. The statistical analysis through factorial arrangements of 2x4, 2x7 and analysis of variance showed that the yield of bologna was higher than that observed for ham. Although it was lower than the control (P < 0.05). The yield with dissolved gum was higher than that obtained for the solid gum. The wheat flour and the starch improved the yield of cooked ham significantly. Cedrela odorata gum exudate, under the used experimental conditions, did not improve the yield and the stability of the low fat meat products.